Polymerase delta deficiency causes syndromic immunodeficiency with replicative stress - (:unkn) unknown (AMER SOC CLINICAL INVESTIGATION INC, 2019)
Polymerase delta is essential for eukaryotic genome duplication and synthesizes DNA at both the leading and lagging strands. The polymerase delta complex is a heterotetramer comprising the catalytic subunit POLD1 and the accessory subunits POLD2, POLD3, and POLD4. Beyond DNA replication, the polymerase delta complex has emerged as a central element in genome maintenance. The essentiality of polymerase delta has constrained the generation of polymerase delta-knockout cell lines or model organisms and, therefore, the understanding of the complexity of its activity and the function of its accessory subunits. To our knowledge, no germline biallelic mutations affecting this complex have been reported in humans. In patients from 2 independent pedigrees, we have identified what we believe to be a novel syndrome with reduced functionality of the polymerase delta complex caused by germline biallelic mutations in POLD1 or POLD2 as the underlying etiology of a previously unknown autosomal-recessive syndrome that combines replicative stress, neurodevelopmental abnormalities, and immunodeficiency. Patients' cells showed impaired cell-cycle progression and replication-associated DNA lesions that were reversible upon overexpression of polymerase delta. The mutations affected the stability and interactions within the polymerase delta complex or its intrinsic polymerase activity. We believe our discovery of human polymerase delta deficiency identifies the central role of this complex in the prevention of replication-related DNA lesions, with particular relevance to adaptive immunity.
Keywords: HOMOLOGOUS RECOMBINATION; GROWTH-RETARDATION; DNA-REPLICATION; SHORT STATURE; ACTIVE-SITE; MUTATION; SUBUNITS; REPAIR; FORKS; INSTABILITY